Spontaneous Combustion of Coal - T. Scully (Canadian Institute of Mining, Metallurgy and Petroleum, 1931)
Since early days in coal mining, it has been known that some coals and the carbonaceous materials associated with them will heat and fire spontaneously. Many theories have been advanced to account for this phenomenon, but it is only within comparatively recent years that any scientific research has been carried out to determine the causes of this heating, the conditions which bring about its occurrence, and the reason why different coals heat with a varying degree of readiness. So far, this research has not cleared up these points entirely, but a great advance has been made in our knowledge of the matter. In general, any coal will fire spontaneously, although with a varying degree of readiness, provided conditions for its doing so are favourable enough. These conditions are that the coal must be in a fine state of division, that sufficient oxygen must be present for rapid oxidation, and that the air current passing must be so small that it is insufficient to carry off the heat produced by this oxidation. Many other minor factors, however, contribute to bring about spontaneous heating, either by producing initial heat themselves or by inducing the other major conditions.